Improved scalar control based on slip compensation from virtual speeds in three-phase induction motor drives - Dinh, Bach Hoang; Tran, Cuong Dinh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The typical scalar control method adjusts the speed based on changes in power frequency while maintaining a constant V/f ratio corresponding to the nominal flux. The disadvantage of the typical scalar method is that the motor operating speed is always less than the reference speed by a slip value. This research proposes an improved scalar control method based on slip compensation for speed control in the induction motor drive. A virtual speed according to the rotor flux-based model reference adaptive system (RF-MRAS) technique is applied to the current model to estimate the proper compensation of the rotor slip. The suitability of the control method is verified through comparative simulations between the typical and proposed methods under various operating conditions by the MATLAB/Simulink software.